ANALYSIS OF DETERMINANTS OF HYPERTENSION IN ADULTS IN KALIBAGOR SUBDISTRICT, BANYUMAS REGENCY - Aryani, Aisyah Apriliciciliana; Mulyani, Jajang Dede; Aryani, Vina Dinata Kamila (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Hypertension is a major risk factor for cardiovascular disease, with increasing prevalence, particularly among the elderly. Genetic and lifestyle factors are believed to contribute to the development of hypertension. This study aimed to examine the relationship between age, family history of hypertension, and smoking behavior with the incidence of hypertension among adults. This cross-sectional study involved 74 adult respondents in Kalibagor Subdistrict, Banyumas Regency. Data were analyzed using chi-square tests and logistic regression. The analysis showed that older age (OR = 3.866; 95% CI: 1.351–11.059) and family history of hypertension (OR = 3.682; 95% CI: 1.974–7.950) were significantly associated with hypertension. Smoking behavior was not significantly associated with hypertension (p > 0.05). Age and family history of hypertension are dominant factors contributing to the incidence of hypertension. Preventive and promotive efforts should focus on high-risk groups to reduce the prevalence of hypertension in the community.